Impact of Membership to Certified Coffee Marketing Cooperatives on the Income of Smallholder Farmers in Jimma Zone of Oromia Region, Ethiopia - Getachew, Zewdu; Beyene, Fekadu; Haji, Jema; Lemma, Tesfaye (International Journal of Economics, 2023)
Purpose: Coffee is one of the most important agricultural commodities with a significant contribution to the growth and well-functioning of Ethiopia's economy, and to the livelihoods of millions of smallholder farmers and laborers. Despite its importance, smallholder coffee production and marketing performance have been unsatisfactory due to various reasons. The introduction of voluntary coffee certification schemes such as Fairtrade (FT) and Organic (Org) certification schemes through cooperatives are viewed as mechanisms to overcome the constraints smallholder farmers face in accessing high value coffee markets and earn better income. However, the impacts of these schemes on the livelihoods of smallholder farmers were not analyzed yet. The main purpose of this study was to estimate the impact of joining (FT, Org or dual FT-Org) certified coffee cooperatives on gross annual incomes earned by member farmers. Methodology: The study employed cross-sectional data collected from randomly selected sample smallholder coffee farmers through a semi-structured questionnaire. Descriptive and simple inferential statistical tests (e.g., frequency, percentage, mean, t-and chi2-tests), and PSM methods were employed to analyze the data. Findings: Results of the descriptive statistics depict that 234 (62.07%) of the total 377 samples farmers were members of certified coffee marketing cooperatives. Among the cooperative members, 83 (35.47%), 84 (35.90%) and 67 (28.63%) were members of FT, Org and dual FT-Org certified coffee marketing cooperatives, respectively. The results of the binary probit model however show that the decisions to join certified coffee marketing cooperatives was significantly influenced by sex, marital status, total livestock holding size, total coffee land size (ha), log total quantity of coffee produced (kg), credit access, and walking distances to development agent's office, coffee marketing center and all-weather road in minutes, respectively. The PSM analysis results show that membership to certified coffee marketing cooperatives has a positive and significant impact on average annual gross income (ETB) earned. The average gross annual income earned by coop member farmers was ETB 14639.15, which is by 36.51% higher than their counterpart non-coop member farmers. The difference is statistically significant at 1% probability level. Unique Contribution to Theory, Practice and Policy: The study recommended that Cooperatives should be encouraged to establish credit and saving units in their internal structure and/or work in collaboration with other saving and credit providing institutions (such as Cooperative Bank of Oromia) to be able to provide demand-driven credit services to member farmers.